Improvement of fatigue resistance of epoxy composite with heterogeneous solidstate self-healing system - Mohd Suzeren Md Jamil,; Wan Naqiuddin Wan Zulrushdi,; Noor Nabilah Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this research study was to investigate the improvement in fatigue life parameters and static strength residues of heterogeneous solid-state of the self-healing resin after exposure to fatigue cycles. The healing system is based on the thermoplastic-thermosetting semi-interpenetrating network. This system employs a thermosetting resin, into which a linear thermoplastic of poly(vinyl chloride) (PVC), poly(vinyl alcohol) (PVA), polyethylene (PE) or polypropylene (PP) as is dissolved. Upon heating a fractured resin system at a specific temperature, the heterogeneous resin blend undergoes a volumetric thermal expansion of healing agent within the matrix resin for crack recovery. Under the Compact tension (CT) test and within the third healing cycle, the modified resin with PVC has the average percentage recovery of 75-48% compared with PP, PE, or PVA at around 67-31%, respectively. The modified epoxy fatigue life with PVC and PP was shown to be increased by a factor of about 1.5 and 1.1 times after healing periods. The healable (modified) resin also showed an improvement in residual strength than the control resin after exposure to fatigue cycles. The fatigue-healing process was proven through the surface and cross-section resin morphology analysis using a microscopy optic and scanning electron microscope (SEM). On the whole, the heterogeneous solid-state selfhealing system has proven to be effective in obstructing fatigue crack propagation, effectively improved the self-healing polymeric material to achieve higher life extension.